2016
DOI: 10.1017/s0029665116000318
|View full text |Cite
|
Sign up to set email alerts
|

Is breakfast the most important meal of the day?

Abstract: 1The Bath Breakfast Project is a series of randomised controlled trials exploring the effects of 2 extended morning fasting on energy balance and health. These trials were categorically not 3 designed to answer whether or not breakfast is the most important meal of the day. However, this The broad field of nutrition and health is rife with myths, misconceptions and frequently 24 posed yet seemingly fundamental questions that we intuitively feel should have simple answers. 25Is a calorie a calorie? Is obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 92 publications
(262 reference statements)
2
55
0
2
Order By: Relevance
“…These studies, alone and when included as part of systematic reviews, have produced inconsistent results [3,16,17] . Recent clinical trials that have examined the association between breakfast consumption and weight have shown that body weights in the breakfast/no-breakfast groups were not different after 6 or 16 weeks [8,18] .…”
Section: Breakfast and Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, alone and when included as part of systematic reviews, have produced inconsistent results [3,16,17] . Recent clinical trials that have examined the association between breakfast consumption and weight have shown that body weights in the breakfast/no-breakfast groups were not different after 6 or 16 weeks [8,18] .…”
Section: Breakfast and Weightmentioning
confidence: 99%
“…How can we know this if we do not know what breakfast is? It is also unclear what is meant by "important" [8] . Important how: To nutrient contribution?…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient deficiencies such as in iron, vitamin A, D, magnesium and zinc, among others, are common in many developing countries and named as "hidden hunger". An important step towards achieving a healthy and rich diet is a regular consumption of breakfast, which provides a higher percentage of micronutrients than other meals [3][4][5][6]. In 1960, Adelle Davis stressed the status of breakfast as the most important meal of the day [7] and later studies detailed that ideally between 15% and 25% of our daily energy intake should be consumed at breakfast [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding breakfast, there are several studies in scientific literature agreeing that the first meal of the day represent an important habit associated with better metabolic health [38,39]. Therefore, public health recommendations regarding breakfast and health advice that people eat breakfast [40].…”
Section: Discussionmentioning
confidence: 99%